Managing and preventing outbreaks of Gram-negative infections in UK neonatal units. Issue 6 (21st June 2013) - Anthony, Mark; Bedford-Russell, Alison; Cooper, Tracey; Fry, Carole; Heath, Paul T; Kennea, Nigel; McCartney, Maureen; Patel, Bharat; Pollard, Tina; Sharland, Mike; Wilson, Peter
Abstract : De novo guidance on the management of Gram-negative bacteria outbreaks in UK neonatal units was developed in 2012 by a Department of Health, England Antimicrobial Resistance and Healthcare Associated Infection working group. The recommendations included activation of an organisational response and establishing a control team when an outbreak is suspected; screening for the specific organism only during an outbreak; undertaking multidisciplinary reviews of cleaning routines, hand hygiene and Gram-negative bacteria transmission risks; considering deep-cleaning; cohorting colonised and infected babies preferably but not necessarily in isolation cubicles; and considering reducing beds or closing a unit to new admissions as a way of improving spacing and staff:patient ratios until the outbreak is under control. The group advised establishing mechanisms to communicate effectively across the network; informing parents of the outbreak as early as possible, and providing prewritten 'infection outbreak' information sheets. For prevention of outbreaks, the group advised meeting national staffing and cot-spacing requirements; following a Water Action Plan; using infection reduction care bundles and benchmarking; and introducing breast milk early and limiting antibiotic use.